Multi-hit damage and perforation of plates inspired by the attacks of the mantis shrimp. (June 2023) - De Falco, P.; Ongaro, F.; Pugno, N.M.
Abstract: The crustacean Odontodactylus scyllarus, known as peacock mantis shrimp, employs its hammer-like appendages to attack and destroy the shells of prey with a sequence of two strikes. The first strong strike of about 480 N triggers a cavitation bubble in the seawater, which provokes a successive hit (about twice weaker than the first one and with a time delay of ≈0.5 ms) on the prey upon collapsing. Inspired by this double-impact strategy, this paper presents a set of parametric finite element simulations of single, double and triple mechanical hits, using elastic-plastic targets and rigid-body projectiles, to compute the damage energy of the target. Several sequences of combinations (strong, weak and equal impact energy), different diameters of the projectile, (3, 4, 6) mm, and various time delays between consecutive impacts, taken in the range 0.0–0.8 ms, are tested by keeping the total impact energy of the projectile fixed and equal to 2.27 J. Our results reveal that: (i) the single-impact strategy is the most damaging, (ii) among the double-impact cases the crustacean attack strategy has the most damaging effect, (iii) the triple-impact strategy shows more complex scenarios and different optimal solutions. Our results could be of interest for designing bio-inspired armours. Highlights: Inspired by the attack of the mantis shrimp, this paper presents a set of simulations of single, double and triple hits. Several sequences of combinations, different diameters of the projectile and various ∆T between impacts are tested. Results reveal as most damaging: (i) the single-impact strategy, (ii) among the double-impact cases, the crustacean attack. Our results could be of interest for designing bio-inspired armours.